FCP - Dongsu Han; Robert Grandl; Aditya Akella; Srinivasan Seshan (ACM SIGCOMM Computer Communication Review, 2013)
Transport protocols must accommodate diverse application and network requirements. As a result, TCP has evolved over time with new congestion control algorithms such as support for generalized AIMD, background flows, and multipath. On the other hand, explicit congestion control algorithms have been shown to be more efficient. However, they are inherently more rigid because they rely on in-network components. Therefore, it is not clear whether they can be made flexible enough to support diverse application requirements. This paper presents a flexible framework for network resource allocation, called FCP, that accommodates diversity by exposing a simple abstraction for resource allocation. FCP incorporates novel primitives for end-point flexibility ( aggregation and preloading ) into a single framework and makes economics-based congestion control practical by explicitly handling load variations and by decoupling it from actual billing. We show that FCP allows evolution by accommodating diversity and ensuring coexistence, while being as efficient as existing explicit congestion control algorithms.